2017
DOI: 10.1111/mmi.13617
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of the molecular chaperone Hsp104 in Saccharomyces cerevisiae results in the malpartition of [PSI+] propagons

Abstract: Summary The ability of a yeast cell to propagate [PSI+], the prion form of the Sup35 protein, is dependent on the molecular chaperone Hsp104. Inhibition of Hsp104 function in yeast cells leads to a failure to generate new propagons, the molecular entities necessary for [PSI+] propagation in dividing cells and they get diluted out as cells multiply. Over‐expression of Hsp104 also leads to [PSI+] prion loss and this has been assumed to arise from the complete disaggregation of the Sup35 prion polymers. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 62 publications
2
72
1
Order By: Relevance
“…However, recent reports have suggested that overexpression of Hsp104 results in malpartition of [PSI ϩ ] propagons (29). Since our results suggest prion-like behavior of aggregated p53 (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…However, recent reports have suggested that overexpression of Hsp104 results in malpartition of [PSI ϩ ] propagons (29). Since our results suggest prion-like behavior of aggregated p53 (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…A recently proposed model states that curing by Hsp104 occurs because it inhibits the severing of the seeds required to initiate templating (48). Another recent report suggests that overexpression of Hsp104 can cause curing due to malpartition of prion propagons, as is observed in the case of [PSI ϩ ] prions (29). Regardless of the models, since we observed prion-like behavior of the aggregated p53, we investigated whether this behavior could be attenuated upon overexpression of Hsp104.…”
Section: Discussionmentioning
confidence: 84%
“…Differential effects of Ydj1 and Sis1 on yeast prions may in turn originate from the differences in their specificities to the Hsp70‐Ssa/Hsp104 substrates (Reidy et al ., ). In combination with Hsp40 and Ssa, Hsp104 is known to catalyze fibril fragmentation (for review, see Chernova et al ., ), however, selective overproduction of Hsp104 antagonizes [ PSI + ], presumably due to defect in prion partitioning during a cell division (see model proposed by Liebman and Chernoff, and supported by data of Winkler et al ., , and Ness et al ., ). As size distribution of Sup35 polymers is not altered by overproduction of Cur1 (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This conclusion corroborates previous observations that fragmentation of Sup35 prion polymers may occur even at low levels of Sis1 (Higurashi et al ., ), while overproduction of Sis1 increases curing of [ PSI + ] by excess Hsp104 (Kryndushkin et al ., , confirmed for our strains by N. Romanova and Y. Chernoff, unpubl. data), a process that, according to Ness et al ., , depends on polymer mispartitioning. Consistently, various non‐lethal mutations in Sis1 as well as substitution of Sis1 by its mammalian homolog counteract loss of [ PSI + ] in the presence of excess Hsp104 (Kirkland et al ., ; Sporn and Hines, ).…”
Section: Discussionmentioning
confidence: 99%
“…A third group posits assymetric segregation of prion seeds that have been collected by the overproduced Hsp104, with some cells emerging from the division with no seeds (51). There is substantial evidence for each of these models.…”
mentioning
confidence: 99%